Penerapan Metode Jigsaw Leasrning terhadap Peningkatan Hasil Belajar Mata Pelajaran Fiqih Peserta Didik Kelas X Studi pada MAN Kotabumi - Andiyanto, Tri (Tapis: Jurnal Penelitian Ilmiah, 2018)
The purpose of this research is to know the improvement of learning outcomes of learners using Jigsaw Learning model on the subjects of Fiqh class X: Study on MAN Kotabumi. This research is a Classroom Action Research (PTK) which is carried out in MAN Kotabumi class X students, amounting to 37 students. This research was designed in two cycles consisting of: (1) Planning, to plan the learning activities and prepare the research instrument, (2) Implementation, that is to carry out the learning activities in class by using Jigsaw Learning model on Fiqih subjects, (3) Observation, data collection through observation sheet and learning result test, (4) Reflection, that is analyzing observation result and data analysis using the average formula. Based on the learning outcomes of learners after using the learning model Jigsaw Learning has increased. This can be seen from the improvement of students' learning mastery in the first cycle of 58.33% and the second cycle of 83.33%. So this means an increase of 25%. From the analysis of data can be understood that the type of learning model Jigsaw Learning can improve learning outcomes in the subjects Fiqih. It can be concluded that the learning model Jigsaw Learning can improve the learning activity between educators and learners, because the materials and methods used are appropriate and more varied so that can be used as further input. Therefore, it can be an alternative that can contribute thoughts and information to educators, principals, and learners in improving learners' learning outcomes through Jigsaw Learning learning method.